2021
DOI: 10.1186/s10020-021-00347-7
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA DKFZp434J0226 regulates the alternative splicing process through phosphorylation of SF3B6 in PDAC

Abstract: Background Long noncoding RNAs (lncRNAs), a type of pervasive genes that regulates various biological processes, are differentially expressed in different types of malignant tumors. The role of lncRNAs in the carcinogenesis of pancreatic ductal adenocarcinoma (PDAC) remains unclear. Here, we investigated the role of the lncRNA DKFZp434J0226 in PDAC. Methods Aberrantly expressed mRNAs and lncRNAs among six PDAC and paired non-tumorous tissues were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Numerous lncRNAs have been identified with elevated expression levels in cancerous tissues and are significantly associated with PNI (Table 2). For instance, lncRNAs such as DKFZp434J0226, FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1), and actin filament-associated protein1-antisense RNA1 (AFAP1-AS1) in PDAC [78][79][80]; opioid growth factor receptor pseudogene 1 (OGFRP1) and HOXA transcript at the distal tip (HOTTIP) in Pca [56,81]; pseudogene 3 of ubiquitin-conjugating enzyme 2C (UBE2CP3), ATMIN-4:2, and gastric cancer associated transcript 2 (GACAT2) in GC [59,82,83]; and translation regulatory long non-coding RNA 1 (TRERNA1), activated by transforming growth factor-β (ATB), and cytoskeleton regulator RNA (CYTOR) in CRC [58,84,85] not only demonstrate high expression in tumor tissues but also exhibit a strong correlation with negative clinical prognostic indicators, such as PNI, OS, lymphovascular invasion, and metastasis. Conversely, the lncRNA AA174084 represents an exception to this trend.…”
Section: Lncrnas Involving In Pni In Cancermentioning
confidence: 99%
“…Numerous lncRNAs have been identified with elevated expression levels in cancerous tissues and are significantly associated with PNI (Table 2). For instance, lncRNAs such as DKFZp434J0226, FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1), and actin filament-associated protein1-antisense RNA1 (AFAP1-AS1) in PDAC [78][79][80]; opioid growth factor receptor pseudogene 1 (OGFRP1) and HOXA transcript at the distal tip (HOTTIP) in Pca [56,81]; pseudogene 3 of ubiquitin-conjugating enzyme 2C (UBE2CP3), ATMIN-4:2, and gastric cancer associated transcript 2 (GACAT2) in GC [59,82,83]; and translation regulatory long non-coding RNA 1 (TRERNA1), activated by transforming growth factor-β (ATB), and cytoskeleton regulator RNA (CYTOR) in CRC [58,84,85] not only demonstrate high expression in tumor tissues but also exhibit a strong correlation with negative clinical prognostic indicators, such as PNI, OS, lymphovascular invasion, and metastasis. Conversely, the lncRNA AA174084 represents an exception to this trend.…”
Section: Lncrnas Involving In Pni In Cancermentioning
confidence: 99%
“…In fact, one study indicated that lncRNAs are sometimes not properly spliced and 3′ end processed due to splicing inefficiency, which contrasts with mRNA splicing efficiency [ 24 ]. Some lncRNAs may regulate splicing, recently, Li et al discovered that lncRNA DKFZp434J0226 promotes phosphorylation of splicing factor SF3B6, which regulates pre-mRNA alternative splicing and promotes pancreatic ductal adenocarcinoma (PDAC) carcinogenesis [ 30 ]. Non-coding RNAs are also known to alter gene expression and disease progression by binding protein complexes.…”
Section: Long Non-coding Rna Molecular Mechanisms and Cancer Involvementmentioning
confidence: 99%
“…In fact, one study indicated that lncRNAs are sometimes not properly spliced and 3' end processed due to splicing inefficiency, which contrasts with mRNA splicing efficiency [22]. Some lncRNAs may regulate splicing, recently, Li et al discovered that lncRNA DKFZp434J0226 promotes phosphorylation of splicing factor SF3B6, which regulates pre-mRNA alternative splicing and promotes pancreatic ductal adenocarcinoma (PDAC) carcinogenesis [28]. Non-coding RNAs are also known to alter gene expression and disease progression by binding protein complexes.…”
Section: Lncrna Nuclear Accumulation Splicing and Gene Regulationmentioning
confidence: 99%